Comparing hospital outcomes between open and closed tibia fractures treated with intramedullary fixation. Issue 7 (July 2017) - Smith, Evan J.; Kuang, Xiangyu; Pandarinath, Rajeev
Abstract: Introduction: Tibial shaft fractures comprise a large portion of operatively treated long bone fractures, and present with the highest rate of open injuries. Intramedullary fixation has become the standard of care for both open and closed injuries. The rates of short term complications and hospital length of stay for open and closed fractures treated with intramedullary fixation is not fully known. Previous series on tibia fractures were performed at high volume centers, and data were not generalizable, further they did not report on length of stay and the impact of preoperative variables on infections, complications and reoperation. We used a large surgical database to compare these outcomes while adjusting for preoperative risk factors. Methods: Data were extracted from the ACS-NSQIP database from 2005 to 2014. Cases were identified based on CPT codes for intramedullary fixation and categorized as closed vs open based on ICD9 code. In addition to demographic and case data, primary analysis examined correlation between open and closed fracture status with infection, complications, reoperation and hospital length of stay. Secondary analysis examined preoperative variables including gender, race, age, BMI, and diabetes effect on outcomes. Results: There were 272 cases identified. There were no significant demographic differences between open and closed tibia fracture cases. Open fracture status did not increase the rate of infection, 30 day complications, reoperation, or length of stay. The only preoperative factor that correlated with length of stay was age. There was no correlation between BMI, presence of insulin dependent and nondependent diabetes, and any outcome measure. Discussion: When considering the complication rates for open and closed tibial shaft fractures treated with intramedullary fixation, there is no difference between 30-day complication rate, length of stay, or return to the operating room. Our reported postoperative infection rates were comparable to previous series, adding validity to our results. The heterogeneity of the hospitals included in ACS-NSQIP database allow our data to be generalizable. These methods may underrepresent the true occurrence of infection as operatively treated tibia infections may present late, requiring late revision. Despite limitations, the data reflect on the current burden of managing these once devastating injuries.